2000
DOI: 10.2307/177205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Synchrony with Host Plant on Populations of a Spring-Feeding Lepidopteran

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.Abstract. Comparisons of traits of outbreaking and nonoutbreaking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…As a result, it is possible that an elevation-temperature cline could decouple the timing of gypsy moth hatching from budburst. However, Hunter and Elkinton (2000) experimentally studied the consequences of such decoupling and found that effects of the timing of budburst and natural enemy induced mortality were opposing; thus, these effects may tend to cancel each other out and the overall impact of seasonal decoupling may be minimal in this system.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it is possible that an elevation-temperature cline could decouple the timing of gypsy moth hatching from budburst. However, Hunter and Elkinton (2000) experimentally studied the consequences of such decoupling and found that effects of the timing of budburst and natural enemy induced mortality were opposing; thus, these effects may tend to cancel each other out and the overall impact of seasonal decoupling may be minimal in this system.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the Moran effect may also synchronize gypsy moth populations via direct effects of weather on gypsy moth survival. For example, cold winter temperatures can kill eggs (Smitley et al 1998), or cool spring temperatures can result in poor synchrony between larval populations and host plant development (Hunter and Elkinton 2000).…”
Section: Outbreak Synchronymentioning
confidence: 99%
“…Optimal conditions for the development of the moth larvae are achieved if they hatch in synchrony with budburst of their host plant. If hatching occurs before budburst, the larvae may starve to death, whereas late hatching implies reduced growth and survival since leaf quality drops rapidly with leaf maturation (Rockwood 1974;Feeny 1976;Ayres and MacLean 1987;Kaitaniemi et al 1997;Van Dongen et al 1997;Hunter and Elkinton 2000;Riipi et al 2002). Consequently, it has been proposed that rapid climate change can cause a mismatch between larval hatching and budburst (Dewar and Watt 1992;Harrington et al 1999;Visser and Holleman 2001).…”
Section: Introductionmentioning
confidence: 99%